2021
DOI: 10.1002/celc.202100476
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Electrocatalytic Performance of Metal Complexes for CO2 Reduction

Abstract: The mass scale catalytic transformation of carbon dioxide (CO2) into reduced forms of carbon is an imperative to address the ever‐increasing anthropogenic emission. Understanding the mechanistic routes leading to the multi‐electron‐proton conversion of CO2 provides handles for chemists to overcome the kinetically and thermodynamically hard challenges and further optimize these processes. Through extensive electrochemical investigations, Prof. J.‐M. Savéant and coworkers have made invaluable electro‐analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…This anodic shift follows the π-delocalization trend of the Fe-Por reported above. 46–48 Furthermore, the faradaic efficiency for CO (FE CO ) is higher for Fe-TBTPP than for either Fe-TPP or Fe-TbcTPP across the entire potential range (Fig. 3b and S5†), with a maximum of 91% at −0.55 V vs. RHE.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This anodic shift follows the π-delocalization trend of the Fe-Por reported above. 46–48 Furthermore, the faradaic efficiency for CO (FE CO ) is higher for Fe-TBTPP than for either Fe-TPP or Fe-TbcTPP across the entire potential range (Fig. 3b and S5†), with a maximum of 91% at −0.55 V vs. RHE.…”
Section: Resultsmentioning
confidence: 98%
“…[25][26][27] Molecular components offer additional versatility compared to metals because their electronic and structural features can be tuned via synthetic modications. [28][29][30][31] While the examples are still limited, studies in the literature on tandem catalysts including CO-producing molecular catalysts and Cu are encouraging. [25][26][27] For example, the addition of either an iron porphyrin or a cobalt phthalocyanine to sputtered Cu resulted in enhanced C 2+ product yields.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of chemical functionalities in the second coordination shell to establish local proton sources, hydrogen bond relays, and electrostatic activators in the vicinity of the active site has led to unprecedented enhancement in the catalytic properties. [24][25][26][27] Herein, we take a closer inspection to the rarely investigated bimetallic strategy (homo-vs hetero-bimetallic) in activating and reducing CO 2 .…”
Section: Molecular Bimetallic Catalystsmentioning
confidence: 99%
“…141,205,210,212 However, the effects exerted by second-sphere substituents seem to play a significant role as suggested by several recent reports. 114,[213][214][215] Therefore, it is imperative to consider those effects which may contribute to the efficiency of -COOH decorated molecular catalysts. Based on mechanism studies, molecular catalysts substituted with hydroxyl (-OH), amino (-NH2), carboxylic (-COOH) groups have been shown to behave as proton donors or Hbond donors during CO2 adsorption by central metal atom and its subsequent conversion to *COOH.…”
Section: Electrochemical Tests: Fe and Current Densitymentioning
confidence: 99%
“…Recent studies have shown that the position of functional group in this second sphere also plays an important role towards performance enhancement by modulating the electronic structure and affecting the ability of the catalyst molecules to interact with CO2 and its intermediates. 38,214 Substituents in the second coordination sphere may play the role of proton donor, 222 stabilize CO2 and reaction intermediates via Hbonding, 117 exert through-space electrostatic effects, 123 or exert inductive/mesomeric effects. 223 Ortho position on phenyl rings of second coordination sphere has typically been shown to improve the catalytic performance due to its proximity to the catalytic sites resulting into enhanced ability to exert various effects.…”
Section: Tuning Of Second Coordination Spherementioning
confidence: 99%